2018
DOI: 10.3389/feart.2018.00144
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Turbulent Fluxes in the Surface Energy Balance of a Debris-Covered Glacier in the Himalayas

Abstract: Surface energy balance models are common tools to estimate melt rates of debris-covered glaciers. In the Himalayas, radiative fluxes are occasionally measured, but very limited observations of turbulent fluxes on debris-covered tongues exist to date. We present measurements collected between 26 September and 12 October 2016 from an eddy correlation system installed on the debris-covered Lirung Glacier in Nepal during the transition between monsoon and post-monsoon. Our observations suggest that surface energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 69 publications
(111 reference statements)
2
75
0
Order By: Relevance
“…Ice surface z 0 was generally larger than snow surface and smaller than patch snow-covered surface. Our results match values reported in studies reporting results ranging from 0.1 to 6.9 mm in Qilian mountain glaciers (Guo et al, 2018;Sun et al, 2018). Our results showed that z 0 reached its maximum at the end of the summer melt, which matched wind profile measurements by Smeets and Broeke (2008).…”
Section: Spatial and Temporal Variability Of Zsupporting
confidence: 92%
See 2 more Smart Citations
“…Ice surface z 0 was generally larger than snow surface and smaller than patch snow-covered surface. Our results match values reported in studies reporting results ranging from 0.1 to 6.9 mm in Qilian mountain glaciers (Guo et al, 2018;Sun et al, 2018). Our results showed that z 0 reached its maximum at the end of the summer melt, which matched wind profile measurements by Smeets and Broeke (2008).…”
Section: Spatial and Temporal Variability Of Zsupporting
confidence: 92%
“…Agisoft Photoscan Professional is a commercial package, which implements all stages of photogrammetric processing (James et al, 2017). It has previously been used to generate three-dimensional point clouds and digital elevation models of debris-covered glaciers (Miles et al, 2017;Quincey et al, 2017;Steiner et al, 2018), ice surfaces and braided meltwater rivers (Javernick et al, 2014;Smith et al, 2016). In our study, we found that after new snowfall it was difficult to match feature points in the photo sets.…”
Section: Data Processingmentioning
confidence: 88%
See 1 more Smart Citation
“…Knowledge about actual debris thickness is limited to few field obser-T. van Woerkom et al: Sediment supply from lateral moraines to a debris-covered glacier in the Himalaya vations (Nicholson and Benn, 2006;Ragettli et al, 2015;McCarthy et al, 2017) and attempts to derive it from thermal bands of satellite imagery (Mihalcea et al, 2008;Pfeffer et al, 2014;Rounce and McKinney, 2014;Schauwecker et al, 2015;Rounce et al, 2018). Several studies suggest that glaciers with prolonged periods of negative mass balance are associated with an increase in debris cover (Deline, 2005;Mihalcea et al, 2006;Stokes et al, 2007;Shukla et al, 2009;Kirkbride and Deline, 2013;Gibson et al, 2017a). Glaciers that have a neutral or positive mass balance, such as in the Karakoram in Pakistan, do not show any positive trends in debris-covered area (Herreid et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially significant as this moisture, along with moisture from precipitation events, can impact the bulk thermal properties of the layer (Nicholson and Benn, 2012). Latent heat flux measured at other debris-covered glaciers shows a stronger and more consistent diurnal variability than is seen at Suldenferner, and typically remains negative during ablation season conditions (Collier and others, 2014;Yao and others, 2014;Steiner and others, 2018). This again could potentially be a result of lower nocturnal surface temperatures over Suldenferner due to the thin debris cover.…”
mentioning
confidence: 96%